ELECTROENCEPHALOGRAPHIC FEATURES IN PATIENTS WITH BRUXISM - N. V. Yurieva; N. N. Maslova; P. N. Geletin; E. I. Boykova (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: bruxism disease polietiological nature manifested injury neuromuscular complex dentition, followed by serious violations. Mechanisms of parafunction masticatory muscles are not fully open. Study of factors that lead to bruxism, is a method of early detection of the disease and prevention of serious complications. The specific features of EEG data in patients with bruxism in order to identify the correlation of functional changes in brain activity and muscle dysfunction.